Anaerobic Digestion of Lignocellulosic Waste Materials - Vasiliki Kamperidou (MDPI AG, 2021)
Nowadays, the climate mitigation policies of EU promote the energy production based on renewable resources. Anaerobic digestion (AD) constitutes a biochemical process that can convert lignocellulosic materials into biogas, used for chemical products isolation or energy production, in the form of electricity, heat or fuels. Such practices are accompanied by several economic, environmental and climatic benefits. The method of AD is an effective method of utilization of several different low-value and negative-cost highly available materials of residual character, such as the lignocellulosic wastes coming from forest, agricultural or marine biomass utilization processes, in order to convert them into directly usable energy. Lignin depolymerization remains a great challenge for the establishment of a full scale process for AD of lignin waste. This review analyzes the method of anaerobic digestion (biomethanation), summarizes the technology and standards involved, the progress achieved so far on the depolymerization/pre-treatment methods of lignocellulosic bio-wastes and the respective residual byproducts coming from industrial processes, aiming to their conversion into energy and the current attempts concerning the utilization of the produced biogas. Substrates’ mechanical, physical, thermal, chemical, and biological pretreatments or a combination of those before biogas production enhance the hydrolysis stage efficiency and, therefore, biogas generation. AD systems are immensely expanding globally, especially in Europe, meeting the high demands of humans for clean energy.